Factors associated with practice of breast self-examination among female teachers of national secondary schools in Ipoh, Perak, Malaysia - Mohd Arif, Fatimah (2018)
Millions of people in this world suffer from cancer. Malaysia is one of those developing countries affected by a high incidence of breast cancer. Therefore, promoting Breast Self-Examination as part of breast cancer awareness programme is important. Breast self-examination will raise awareness about breast cancer and women breast health which are an important contribution to early detection effort. The objective of this study is to determine the factors associated (socio-demographic characteristics, knowledge, belief, access to breast health promotion programme, and breast health history of respondent) with the practice of breast self-examination among female teachers of national secondary schools in Ipoh City, Perak. This is a cross-sectional study among female teachers in Ipoh, Perak. A random sampling method was used to select eligible female teachers in national secondary schools in Ipoh City, Perak. A total of 510 teachers were included in this study. A validated and reliable self-administered questionnaire was used in this study. The questionnaire obtained information on sociodemographic characteristics, breast health history of the respondent (personal history of breast disease and family history of breast cancer), access to breast health promotion programme, knowledge and beliefs concerning breast cancer and breast self-examination. Results in this study indicated that the majority of the respondents 388 (76.1%) practise breast self-examination. Most of them were between 41 and 50 years old with the mean age of 41.20±8.79. Only 111 (21.8%) respondents had a family history of breast cancer while 38 (7.5%) had a personal history of breast disease. Overall, this study revealed that most information about breast cancer was provided by health professionals and only minority of respondents went to a previous education programme. According to this study, there were association between knowledge on signs and symptoms of breast cancer (t=-2.95, p=0.004), risk factors of breast cancer (t=-3.15, p=0.002) and knowledge on breast self-examination (t=-5.01, p<0.0001) with breast self-examination practice. Findings of this study also showed significant association between perceived benefits (t=-2.59, p=0.01), perceived barriers (t=-2.64, p=0.008), confidence (t=-6.74, p<0.0001) and health motivation (t=-3.09, p=0.002) with practice of breast self-examination. Multiple logistic regression analysis yielded four significant predictor variables. In conclusion, the proportion of female teachers practising breast self-examination was high (76.1%). The factors contributing to practise breast self-examination in this study were marital status, personal history of breast disease, access towards breast health promotion programme such as respondent ever attended previous breast cancer education programme, doctor ever recommended breast self-examination, doctor ever trained proper breast self-examination techniques, doctor ever talk about early detection of breast cancer and respondent ever checked any breast disease by doctors, knowledge, and belief (perceived benefits, perceived barriers, confidence and health motivation). These variables were found to have a significant association with breast self-examination practice. Hopefully, the results can be a baseline for future intervention in attempts to increase breast self-examination practice. This study also suggested by educating respondents with the knowledge that made them understand and aware of breast cancer and the value of breast self-examination. Hence, it is important to plan a strategy based on valuable information gained from this study to develop targeted health education which in turns would have the impacts on the population.